Comparative Analysis of Stability Control Strategy from Grid-connected to Island Operation Based on VSC-HVDC System - CHEN Qi-chao; LI Hui; LIU Jian-qin; WANG Fei; MENG Jing-wei (Journal of Harbin University of Science and Technology)
The frequency stability problem and frequency transient characteristics of the system under the island operation mode formed by AC tie-line N-2 faults are analyzed after the power grid is evolved into an asynchronous interconnection using VSC-HVDC. The most serious case of frequency problem is selected to study the transient characteristics and to clarify the main influencing factors，on the basis of giving detailed stability control measures from grid-connected to island operation. The comparison between generator tripping and power emergency control is analyzed，and the result shows that both of the two strategies can effectively improve the stability of the island system，but the generator tripping is superior to the power emergency control in improving the frequency transient characteristics. Finally，the electromagnetic transient simulation model of Chongqing-Hubei back-to-back VSC-HVDC project was built as an example to verify the conclusion，and the pre-control range of the AC tie line for ensuring the stable operation was also proposed.